The Training on Making Simple Financial Reports in the Sempakata Village, Medan Selayang District - Hendrik E.S Samosir; Martin Luter Purba; Hanna M. Damanik (PT FORMOSA CENDEKIA GLOBAL, 2023)
This training aims to increase public awareness of making simple financial reports for small and medium enterprises. The results of this training are expected to increase participants' knowledge about the positive impact of making simple financial reports when running a business. The training is carried out by giving lectures on simple financial reports and directly training the participants to make simple financial reports. The results of this training show the enthusiasm of the participants to apply the training material to the businesses they are currently running. In addition, most of the participants felt that the material provided had succeeded in changing their thinking about simple financial reports.